Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium

Covalently anchored ruthenium-phosphine complex on mesoporous organosilica: catalytic applications in hydrogenation reactions - Sisodiya, Sheetal; Lazar, Anish; Shylesh, Sankaranarayanapillai; Wang, Lei; Thiel, Werner R.; Singh, Anand Pal (Catalysis Communications, 2012)
New heterogeneous catalysts for alkene hydrogenation reactions were prepared by the immobilization of trimethoxysilane functionalized triphenylphosphine eta(6)-p-cymene ruthenium complex on mesoporous organosilica (PMO-Ru). Characterization techniques confirmed the structural integrity of the organosilica material and proved the successful anchoring of ruthenium complex. Catalytic activity and stability of PMO-Ru sample investigated in the hydrogenation of various olefins showed higher activity than a neat and MCM-41 supported ruthenium catalyst. High catalytic activity and stability of organosilica supported ruthenium catalyst are attributed to the hydrophobic environments and to the unique structural features imparted from the presence of organic groups in the framewall positions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Heterogenization; Hydrogenation; Organosilica; ruthenium; Triphenyl phosphine

Electrostatic grafting of a triphenylphosphine sulfonate on SBA-15: application in palladium catalyzed hydrogenation - Wang, Lei; Dehe, Daniel; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Zhou, Zhou; Hartmann, Martin; Taylor, Robin N. Klupp; Singh, Anand Pal; Jia, Mingjun; Thiel, Werner R. (Catalysis Science & Technology, 2012)
A novel strategy for the immobilization of a sulfonate functionalized triphenylphosphine ligand by ion-ion interactions on an imidazolium modified SBA-15 is presented. A support containing electrostatically grafted triphenylphosphine as the ligand was reacted with PdCl2( CNPh)(2) and the resulting hybrid material catalyzed olefin hydrogenation under mild conditions. The catalyst exhibits excellent activity, selectivity and stability and it can be reused for at least ten times without any loss of activity. An analogous but covalently grafted palladium system does not show any hydrogenation activity under the same conditions. TEM images of the used catalyst clearly prove the absence of palladium nanoparticles. Additionally, XPS investigations prove that palladium( 0) is formed and the phosphine is oxidized. By AAS no palladium contamination down to 0.5 X 10(-4) mmol could be detected in the products and further leaching tests verified the reaction to be truly heterogeneous. This concept of non-covalent immobilization guarantees a tight bonding of the catalytically active species to the surface in combination with a high mobility, which should be favorable for other catalyses, too.

Synthesis and characterization of 3-[N,N `-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15: a highly stable and reusable catalyst for epoxidation and sulfoxidation reactions - Lazar, Anish; Thiel, Werner R.; Singh, A. P. (RSC Advances, 2014)
The efficient and reusable oxidation catalyst 3-[N,N'-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15 has been synthesized by the anchoring of the 3-[N,N-bis-3-(salicylidenamino)ethyltriamine] ligand (L or Salpr) on the inner surfaces of organofunctionalized SBA-15 and subsequent complexation with Mo(VI) O-2(acac)(2). The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2-sorption measurements, TG & DTA, solid state C-13, Si-29 NMR spectroscopy, FT-IR, Raman spectroscopy, XPS, DRS UV-Vis spectroscopy, SEM and TEM. XRD and N-2 sorption analyses helped to find out the morphological and textural properties of the synthesized catalysts and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide hints of a good structural stability, the existence of long range ordering and a high pore wall thickness. TG and DTA results reveal that the thermal stability of (L)Mo(VI)O-2@SBA-15 was maintained up to 300 degrees C. The organic moieties anchored over the surface of the SBA-15 support were determined by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides the information about the degree of functionalization of the surface silanol groups with the organic moiety. The electronic environment and the oxidation state of the molybdenum site in (L)Mo(VI)O-2@SBA-15 were monitored by Raman spectroscopy, XPS and DRS UV-Vis techniques. Moreover, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalysts were evaluated in epoxidation and sulfoxidation reactions, and the results show that (L)Mo(VI)O-2@SBA-15 exhibits high conversion and selectivity towards epoxidation and sulfoxidation reactions in combination with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity. In addition, Sheldon's hot filtration test was also carried out.